Improving The Capacity of Village Officials Using Digitalization for Vulnerable People Disaster Area - Damayanti Wardyaningrum; Endang Ripmiatin; Ade Jamal; Ani Isnaeni; Dani Kuntowibisono (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2026)
Sukanagalih Village in Cianjur, West Java is one of the villages located in an area prone to earthquake disasters. The 2022 earthquake in Cianjur claimed the lives of more than five hundred people, and thousands of refugees required major efforts to mitigate disaster risks. This region urgently needs to manage population data with digitalization for the purpose of disaster mitigation. Especially identifying the residents who are included into the category of vulnerable people affected by disasters, such as toddlers, children, pregnant women, the elderly and the disabled. In the event of the 2022 disaster, the distribution of aid to vulnerable people was inadequate due to the unavailability of data that can be readily accessed by the benefactors. This community service program aims to improve the capacity of village officials in managing population data, especially for disaster-prone groups through the digitalization. The activities in this program consisted of compilation of population data materials, creation of a digital application, implementation of the training program and evaluation of the activities. These activities received very good responses from the training participants, who were village officials from all elements, and there were a number of requests, wishing improvement to several features in the digital application.